ESRA19-0246 Regional anesthesia combined with virtual reality hypnosis for an extended orthopedic procedure in a patient with severe symptomatic aortic valve stenosis: a case report. (30th August 2019) - De Schrijver, L; Sermeus, L; Maes, S; Camerlynck, H; Morrison, S; Van Glabbeek, F
Abstract : Background and aims: Virtual reality hypnosis (VRH) is a combination of visual immersion in a virtual reality environment and verbal hypnosis. VRH can be used in addition to conventional techniques for sedation and pain management during wound care. Patients undergoing painful and long-lasting procedures under regional anesthesia could also benefit from this technique. Methods: Case report: A 69-year old man (we obtained patient's consent for publication of this case report), with a previous medical history of arterial hypertension, COPD and severe symptomatic aortic valve stenosis (ø0.69 cm 2 with a max/mean gradient of 91/58mmHg) sustained a proximal humerus fracture-dislocation during a syncopic episode. He was therefore scheduled to undergo hemi-arthroplasty. Anesthesia was provided with ultrasound-guided continuous interscalene block at the C5-C6 level (11 mL levobupivacaine 0.5%) combined with a single-shot superficial cervical plexus block (6 mL levobupivacaine 0.5%). Since the patient needed to be immobilized in the beach chair position for approximately 2 hours, we used VRH to induce sedation and improve comfort without using medication (figure 1 ). VRH was provided by headphones and head-mounted goggles, showing computer generated images of underwater scenes (Aqua module, Oncomfort™). Results: Surgery was uneventful and lasted for 90 minutes, during which time hemodynamic stability was maintained. The patient remained calm and could interact with the anesthesiologist, answering questions when necessary. He reported no pain during the procedure. No sedative drugs were given before or during the procedure. Conclusions: Non-pharmacological sedation can be achieved with VRH. This option can be offered to patients undergoing extended surgery under regional anesthesia.